Economic feasibility study for the production and marketing of medicinal and aromatic plants (Municipal mint model) in Lattakia Governorate - عليو محمود; شعباني باسل (Latakia University Journal -Biological Sciences Series, 2021)
Cultivation of medicinal and aromatic plants (the municipal mint plant) is one of the alternative economic crops in Syria due to the suitability of the natural and environmental conditions for their cultivation, as this study was conducted on all field-counted farmers in Lattakia Governorate, and their number reached 317 farmers, with a cultivated area of ​​177 dunums in 2020. This research aims to achieve the following: 1- Analysis of the production costs of producing and marketing the municipal mint plant in Lattakia Governorate. 2- The economic calendar for the production and marketing of the municipal mint plant in Lattakia Governorate. The study revealed the following results: 1- The annual net profit achieved in one dunum of cultivated mint plants in Lattakia governorate reached 769436.3 SP. 2- The net income of the farmer per dunum planted with the municipal mint plant in Lattakia Governorate was 848391.6 SP. 3- The total economic efficiency of producing and marketing the municipal mint plant in Lattakia governorate reached 1.75, which is more than one, which indicates the feasibility of the project..